Ultrasound induced green synthesis of pyrazolo-pyridines as novel corrosion inhibitors useful for industrial pickling process - Dohare, Parul; Quraishi, M.A.; Verma, Chandrabhan; Lgaz, H.; Salghi, R.; Ebenso, E.E. (Elsevier B.V., 2019)
Three pyrazolo-pyridine derivatives namely, (PPs)(4-(4-methoyphenyl)3,5-dimethyl-1,4,7,8-tetrahydrodipyrazolopyridine)(PP-1), 3,5dimethyl-4-phenyl-1,4,7,8-tetrahydrodipyrazolopyridine (PP-2)and (3,5-dimethyl-4-(3-nitrophenyl)-1,4,7,8-tetrahyddrodipyrazolopyridine)(PP-3)having different substituents was synthesized using ultrasound mediated one step multicomponent reactions and evaluated as corrosion inhibitors for mild steel in acidic medium of 1 M HCl. Protection ability of the synthesized PPs was determined using several experimental and computational modeling methods. Results showed that PP-3 having electron withdrawing nitro (–NO2)substituent showed lowest inhibition ability and PP-1 having electron releasing methoxy (–OCH3)substituent showed the highest inhibition efficiency. Inhibition efficiencies of the tested PP molecules followed the order: PP-1 (96.4%; –OCH3)> PP-2 (94.2%; –H)> PP-1 (91.1%; –NO2). Electrochemical studies suggested that PPs acted as interface and mixed type of corrosion inhibitors and their adsorption at the metal-electrolyte interfaces obeyed the Langmuir adsorption isotherm model. SEM and AFM analyses were adopted to measure the surface morphology of inhibited and uninhibited metallic surfaces. Experimental results were corroborated by results derived from DFT modeling and MD simulations.
Experimental and theoretical approach
Keywords: Adsorption; DFT; Diffusion model; Inhibition; MD Simulation; Pyrazolopyridine